The curious case of the Mesolithic Iberian dogs: an archaeogenetic study - Pires, Ana Elisabete (2019)
We investigated the genetic, composition of six Canis remains from western Iberia, directly radiocarbon dated to 7,903-7,570 years (cal BP). They were identified as dogs via their qrchaeological and depositional context, osteometry, and a high percentage of aquatic diet shared with humans. For comparison, genetic data were obtained from an additional 37 Iberian dog remains from the Neolithic to Late Antiquity, as well as two Palaeolithic anda a Chalcolithic Canis identified as wolves. Previous data indicated that dog mtDNA haplogroup A (HgA) is prevalent in extant European dogs (>50%), in the Near East and Asia, but rare or absent (<10%) in European Canis older than 3,000 years (cal BP). We found a high frequency of dog HgA in pre-Neolithic Europe. We show that, contrary to the current view, Canis with HgA did not necessarily arrive in Europe from East-Asia. This phylogeographical difference in HgA frequency demonstrates that genetic differentiation was prior to, or as a consequence of, domestication which may be linked with pre-Neolithic local processes for Iberian wolf domestication. Our results emphasize that knowledge of both ancient wolves and early dogs genetic profiles from the European periphery should improve our understanding of the evolution of the European dog.